2022
DOI: 10.1128/cmr.00079-21
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcal Neonatal Meningitis

Abstract: Neonatal bacterial meningitis is a devastating disease, associated with high mortality and neurological disability, in both developed and developing countries. Streptococcus agalactiae , commonly referred to as group B Streptococcus (GBS), remains the most common bacterial cause of meningitis among infants younger than 90 days. Maternal colonization with GBS in the gastrointestinal and/or genitourinary tract is the primary risk factor for neonatal invasive diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 275 publications
0
30
0
Order By: Relevance
“…Although the type III CC17 GBS strain is known to have caused the majority of neonatal invasive diseases in recent decades ( 8 10 , 12 , 13 ), the type Ib CC12 GBS strain has been found to be more virulent and fatal than the type III CC17 strain ( 20 , 22 , 24 , 26 ). Recent reports found a mortality rate of 30.8% in neonates with type Ib CC12 GBS invasive disease ( 24 ), which was much higher than the reported 8.8 to 12% mortality rate associated with GBS invasive diseases caused by other serotypes, including a mortality rate of 12.5 to 18.5% associated with the type III CC17 GBS strain ( 8 10 , 12 , 13 , 27 29 ). Zhang et al and others also found that type Ib CC10 GBS isolates were associated with a significantly higher rate of meningitis and higher illness severity ( 20 22 ).…”
Section: Discussionmentioning
confidence: 75%
“…Although the type III CC17 GBS strain is known to have caused the majority of neonatal invasive diseases in recent decades ( 8 10 , 12 , 13 ), the type Ib CC12 GBS strain has been found to be more virulent and fatal than the type III CC17 strain ( 20 , 22 , 24 , 26 ). Recent reports found a mortality rate of 30.8% in neonates with type Ib CC12 GBS invasive disease ( 24 ), which was much higher than the reported 8.8 to 12% mortality rate associated with GBS invasive diseases caused by other serotypes, including a mortality rate of 12.5 to 18.5% associated with the type III CC17 GBS strain ( 8 10 , 12 , 13 , 27 29 ). Zhang et al and others also found that type Ib CC10 GBS isolates were associated with a significantly higher rate of meningitis and higher illness severity ( 20 22 ).…”
Section: Discussionmentioning
confidence: 75%
“…Many brain cells can produce cytokine and pro-inflammatory proteins when bacterial enter the CSF, these pro-inflammatory proteins include reactive oxygen species (ROS), nitric oxide, peroxynitrite, matrix metalloproteinases (MMPs), platelet activating factor, calcium, etc ( 25 , 26 ). A comparison of BM group with N group, GO analysis showed that the signal pathways that involve these pro-inflammatory proteins in active states in our data.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus agalactiae, categorized in group B Streptococcus, is the most common microorganism causing purulent meningitis among neonates or infants younger than 90 days [124][125][126]. Figure 43 displays Gram-positive cocci phagocytized by neutrophils in the cerebrospinal fluid of a neonate.…”
Section: Purulent Meningitis In the Neonate Caused By Group B Strepto...mentioning
confidence: 99%